New lichen-associated bulbil-forming species of Cantharellales (Basidiomycetes). (12th May 2014) - DIEDERICH, Paul; LAWREY, James D.; CAPDET, Mariana; PEREIRA, Susana; ROMERO, Andrea I.; ETAYO, Javier; FLAKUS, Adam; SIKAROODI, Masoumeh; ERTZ, Damien
Abstract Two new genera and four new species of bulbil-forming basidiomycetes are described. Phylogenetic analyses of nuLSU and ITS sequences place them in Cantharellales. A facultative lichenicolous species with yellow to orange-yellow bulbils from South America groups with the type of Burgella and is consequently described as B. lutea. The new species and genus Burgellopsis nivea is introduced for material from Scotland with white bulbils overgrowing saxicolous lichens. An obligate lichenicolous species with particularly large, applanate bulbils developing over Peltigerales in South America could not be placed accurately using ITS sequences and is described as the new species and genus Bulbilla applanata. A European species with brown, facultatively lichenicolous bulbils grouped with Ceratobasidium and Thanatephorus species and is described as the new Ceratobasidium bulbillifaciens.